2019
DOI: 10.3390/plants8040080
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ozone Sensitivity in Three Wheat Cultivars Using Ethylenediurea

Abstract: Three wheat (Triticum aestivum L.) cultivars [HD 2987 (ozone (O3) sensitive), PBW 502 (intermediately sensitive) and Kharchiya 65 (O3 tolerant)] with known sensitivity to O3 were re-evaluated using ethylenediurea (EDU; 400 ppm) to ascertain the use of EDU in determiningO3 sensitivity under highly O3-polluted tropical environments. EDU treatment helped in improving the growth, biomass, photosynthetic pigments and the antioxidative defense system of all the wheat cultivars. Under EDU treatment, PBW 502 retained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Mean O3 concentration recorded during the experimental period was high enough to cause significant reductions in the agricultural productivity, as evident from the previous works done at the same experimental site (Ghosh et al, 2020;Yadav et al, 2019;Fatima et al, 2019;Singh et al, 2015;Tiwari et al, 2011). The average 8h (M8) O3 concentration during the present study was observed to be 50.5 ppb, with mean monthly M8 O3 concentration varying in the range of 40.17-53.97 ppb.…”
Section: Discussionsupporting
confidence: 80%
“…Mean O3 concentration recorded during the experimental period was high enough to cause significant reductions in the agricultural productivity, as evident from the previous works done at the same experimental site (Ghosh et al, 2020;Yadav et al, 2019;Fatima et al, 2019;Singh et al, 2015;Tiwari et al, 2011). The average 8h (M8) O3 concentration during the present study was observed to be 50.5 ppb, with mean monthly M8 O3 concentration varying in the range of 40.17-53.97 ppb.…”
Section: Discussionsupporting
confidence: 80%
“…Plants were grown under ambient O 3 throughout the 4 growing seasons, in the open-field plots explained earlier (“ Plant material preparation ” section). Exposing plants to only ambient O 3 (with no other O 3 treatment) is a common practice in the research of EDU effects on plants (Oksanen et al 2013 ; Carriero et al 2015 ; Yuan et al 2015 ; Fatima et al 2019 ; Pandey et al 2019 ). Because the ambient O 3 level in Sapporo is relatively low compared to southern areas of the Northern Hemisphere, the plants were subjected to elevated O 3 in the third (23 May to 1 October, 2016) and fourth (18 June to 1 October, 2017) growing seasons.…”
Section: Methodsmentioning
confidence: 99%
“…These results also suggest that EDU mode of action against O 3 damage was rather related to biochemical processes. However, it should be noted that the mode of action of EDU appears to be not only species-specific but also cultivar-or genotypespecific (Singh et al 2015;Jiang et al 2018;Feng et al 2018;Pandey et al 2019;Fatima et al 2019).…”
Section: O 3 and Edu Effects On Gas Exchangementioning
confidence: 99%